Leadership Challenges Facing South African Expatriates Working in Africa - John, Natasha Jayshree (My University, 2013)
The increasing trend of globalisation has implications for companies wanting to do international business as well as for their global talent management approach. As greater interest concentrates on doing business in developing countries, research into leadership challenges associated with this comes under the spot-light as a priority. For this qualitative study fourteen (14) semi-structured interviews were conducted, the findings of which have been categorised into ten (10) interdependent and multi-dimensional themes, covering both personal and professional challenges, thus demanding an integrated and multi-dimensional approach to addressing them. To this end, fifteen (15) recommendations have been proposed to holistically address these leadership challenges, in the form of the proposed “Who-What-How-WOW!” integrated response framework, which, in keeping with the principles of African leadership, prioritises partnerships and collaboration. This study can help different stakeholders better understand their roles in addressing the leadership challenges of South African expatriates working in Africa. This study has also revealed a lack of current research and information to help South African expatriates adjust personally and professionally in other countries in Africa. More research is thus required such that, going forward, it makes a meaningful difference to addressing the leadership challenges facing South African expatriates working in Africa thereby improving their overall experience
MBA thesis
Keywords: Leadership; Ex-patriates working in Africa; Globalisation